Witness : lessons from Elie Wiesel's classroom - Burger, Ariel (Houghton Mifflin Harcourt, 2018)
"[Elie Wiesel] taught at Boston University for nearly four decades, and with this book, Ariel Burger—devoted protégé, apprentice, and friend—takes us into the sacred space of Wiesel's classroom. There, Wiesel challenged his students to explore moral complexity and to resist the dangerous lure of absolutes. In bringing together never-before-recounted moments between Wiesel and his students, Witness serves as a moral education in and of itself—a primer on educating against indifference, on the urgency of memory and individual responsibility, and on the role of literature, music, and art in making the world a more compassionate place."--Dust jacket flap